Impact of diabetes mellitus on procedural and one year clinical outcomes following treatment of severely calcified coronary lesions with the orbital atherectomy system: A subanalysis of the ORBIT II study. Issue 6 (22nd July 2017) - Lee, Michael S.; Martinsen, Brad J.; Lee, Arthur C.; Behrens, Ann N.; Shlofmitz, Richard A.; Kim, Christopher Y.; Chambers, Jeffrey W.
Abstract: Objectives: The goal of the study was to investigate the safety and efficacy of the coronary orbital atherectomy system to treat severe coronary artery calcification (CAC) prior to stent placement in diabetic and non‐diabetic patients. Background: The ORBIT II study reported the safety and efficacy of orbital atherectomy treatment in 443 patients with severe CAC. Percutaneous coronary intervention in diabetic patients is associated with an increased risk of major adverse cardiac events (MACE) compared with non‐diabetics. The outcomes of diabetic patients who undergo orbital atherectomy are unknown. Methods: Patients were sub‐grouped as either diabetic (160/443, 36.1%) or non‐diabetic (283/443, 63.9%). The MACE rate, defined as cardiac death, myocardial infarction (MI; CK‐MB > 3X ULN), and target vessel revascularization, was examined at 30 days and 1 year after treatment. Results: Procedural success was similar in the diabetic and non‐diabetic groups (89.3 vs. 88.6%, P = 0.88). There was no significant difference in the 30‐day and 1‐year MACE rates between the diabetic and non‐diabetic groups (30 day: 8.8 vs. 11.3%; P = 0.40; 1 year: 17.1 vs. 16.7%, P = 0.97). The individual components of cardiac death (3.9 vs. 2.9%, P = 0.58), MI (9.4 vs. 11.3%, P = 0.52), and target vessel revascularization (5.9 vs. 5.8%, P = 0.99) were also similar in both groups at 1 year. Conclusions: The rates of adverse clinical events in diabetic patients who underwent orbital atherectomy were low and similar to non‐diabetic patients. This study suggests orbital atherectomy is a reasonable treatment strategy for diabetic patients with severe CAC.